Clinical researchComparison of the effectiveness of compression stockings and layer compression systems in venous ulceration treatment - Szewczyk, Maria T.; Jawień, Arkadiusz; Cierzniakowska, Katarzyna; Cwajda-Białasik, Justyna; Mościcka, Paulina (Archives of Medical Science, 2010)
Introduction : The aim of the research was to compare the dynamics of venous ulcer healing when treated with the use of compression stockings as well as original two- and four-layer bandage systems. Material and methods : A group of 46 patients suffering from venous ulcers was studied. This group consisted of 36 (78.3%) women and 10 (21.70%) men aged between 41 and 88 years (the average age was 66.6 years and the median was 67). Patients were randomized into three groups, for treatment with the ProGuide two-layer system, Profore four-layer compression, and with the use of compression stockings class II. In the case of multi-layer compression, compression ensuring 40 mmHg blood pressure at ankle level was used. Results : In all patients, independently of the type of compression therapy, a few significant statistical changes of ulceration area in time were observed (Student’s t test for matched pairs, p < 0.05). The largest loss of ulceration area in each of the successive measurements was observed in patients treated with the four-layer system – on average 0.63 cm 2 /per week. The smallest loss of ulceration area was observed in patients using compression stockings – on average 0.44 cm 2 /per week. However, the observed differences were not statistically significant (Kruskal-Wallis test H = 4.45, p > 0.05). Conclusions : A systematic compression therapy, applied with preliminary blood pressure of 40 mmHg, is an effective method of conservative treatment of venous ulcers. Compression stockings and prepared systems of multi-layer compression were characterized by similar clinical effectiveness.